(untitled) (Archives of Criminology, 2023)
In the article we analysed how the introduction and application of life imprisonment in the period of transformation has impacted the development of the penitentiary system to date. We answered how and why the legislature eliminated the death penalty from the catalogue of penalties in the Polish Penal Code of 1997, and replaced it with life imprisonment. We took into account the statistics on life sentences passed in Poland. We present the evolution of the prison system, which for a quarter of a century had to cope with this difcult category of prisoners by fnding new legal solutions and applying international standards. We also discussed some conclusions of the scholarly study ‘Te best of the worst and the still evil: Prisoners serving life sentences’, which has been conducted since 2014 by our research team. Te study focuses on the management and application of this extreme punishment in Poland, the adaptation of prisoners with life sentences to the isolation and social dimension of imprisonment.